Seasonal dimensions of the HIV-hunger nexus in eastern and southern Africa - Gillespie, Stuart; Drimie, Scott (International Food Policy Research Institute, 2009)
The seasonality of disease, ill-health and hunger were illustrated in multiple contexts in the original IDS conference on seasonality over three decades ago. The subsequent book (Chambers et al. 1981) was published in the same year as the first case of AIDS was reported. Since then, the rapidly accelerating AIDS epidemic of the 1990s and its current state of “hyperendemicity” in southern Africa have affected the levels, intensity and nature of vulnerability of households to livelihood shocks and stresses. The food price crisis of 2008 and the ongoing global financial crisis have further impacted the ability of households, communities, and national governments to achieve food security for large numbers of people in the region. Overlaying these dynamics, various manifestations of climate change are beginning to have an impact again, with evidence of interactions with other drivers of vulnerability.